Passenger Flows at Escalators – Arriving at Count Interval for Design Flow Estimation - Kahali, Dharitri; Rastogi, Rajat (European Journal of Transport and Infrastructure Research, 2021)
Selection of a count interval to extract flow data on pedestrian facilities seems to be governed by the operational environment of the facility and context of the study. Based on the flow condition, which may be intermittent, uniform, or periodic, the count interval has been found varying between 1 minute and 5 minutes. For instantaneous peaks, it is reduced to even 10s. The selection of a count interval will impact the flow values and subsequently the design requirements and operational efficiency. Present study, in this light, focusses on escalators located at metro rail stations. The study region is Delhi, India. Based on the analysis, the count interval for data extraction is recommended as 24 seconds, which is expected to result in a flow that does not cause unnecessary increase in facility size and keep it usable for most of the time. The absolute design flow value may be considered between 140–148 ped/m/min, which is the 5th highest rank order peak flow. The results are expected to optimize the resources, both for data collection and size of a facility.